2013
DOI: 10.1258/acb.2012.012122
|View full text |Cite
|
Sign up to set email alerts
|

Demography and biochemistry of 2800 patients from a renal stones clinic

Abstract: Risk factors for stones differ between men and women, change with ageing and in some may have a genetic basis. The role of phosphaturia merits further exploration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 37 publications
4
36
0
4
Order By: Relevance
“…Falling urine pH with age 16 19–21 and a high dietary acid load7 9 11 are contributory. Metabolic studies demonstrated that idiopathic uric acid stone formers are insulin resistant and have an inappropriately low ammonium excretion for their urinary acidity 12 22.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Falling urine pH with age 16 19–21 and a high dietary acid load7 9 11 are contributory. Metabolic studies demonstrated that idiopathic uric acid stone formers are insulin resistant and have an inappropriately low ammonium excretion for their urinary acidity 12 22.…”
Section: Discussionmentioning
confidence: 99%
“…The stones clinic database, held on Microsoft Access (97–2003), was created in 1996 and includes data for most patients investigated for stones risk at their initial presentation to the Renal Stones Clinic of the Clinical Biochemistry Department of Southampton University Hospitals from June 1990 to March 2007 16. The data were anonymised for the research study which was approved by the Regional Ethics Committee.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A clinic database, held on Microsoft Access (97–2003), was created in 1996 and includes demographic and biochemical data for most patients investigated at their initial presentation to the clinic between June 1990 and March 2007 9. The data were anonymised for the research study, which was approved by the regional ethics committee.…”
Section: Methodsmentioning
confidence: 99%